Hierarchical dose–response modeling for high‐throughput toxicity screening of environmental chemicals. Issue 1 (7th January 2014) - Wilson, Ander; Reif, David M.; Reich, Brian J.
Summary High‐throughput screening (HTS) of environmental chemicals is used to identify chemicals with high potential for adverse human health and environmental effects from among the thousands of untested chemicals. Predicting physiologically relevant activity with HTS data requires estimating the response of a large number of chemicals across a battery of screening assays based on sparse dose–response data for each chemical‐assay combination. Many standard dose–response methods are inadequate because they treat each curve separately and under‐perform when there are as few as 6–10 observations per curve. We propose a semiparametric Bayesian model that borrows strength across chemicals and assays. Our method directly parametrizes the efficacy and potency of the chemicals as well as the probability of response. We use the ToxCast data from the U.S. Environmental Protection Agency (EPA) as motivation. We demonstrate that our hierarchical method provides more accurate estimates of the probability of response, efficacy, and potency than separate curve estimation in a simulation study. We use our semiparametric method to compare the efficacy of chemicals in the ToxCast data to well‐characterized reference chemicals on estrogen receptor <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4ss8mt1v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> (ER<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4ss8mt09" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>) and peroxisome proliferator‐activated receptor <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4ss8msw4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> (PPAR<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4ss8msvk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>) assays, then estimate the probability that other chemicals are active at lower concentrations than the reference chemicals.